Simulation Training in Psychiatry for Medical Education: A Review - Piot, Marie-Aude; Attoe, Chris; Billon, Gregoire; Cross, Sean; Rethans, Jan-Joost; Falissard, Bruno (Frontiers in Psychiatry, 2021)
Despite recognised benefits of Simulation-based Education (SBE) in healthcare, specific adaptations required within psychiatry has slowed its adoption. This article discusses the historical, theoretical, and practical features of SBE in psychiatry that highlight potential opportunities and controversies. SBE has been influenced by the aviation industry and early adopting medical specialties, alongside role play and patient educators. Concurrently, healthcare has shifted towards patient-centred approaches and healthcare education has prioritised reflective learning and an understanding of variable learner experiences. Consequently, SBE is particularly focused on a holistic approach to care, reflective learning, an awareness of emotions in interactions and learning, cognitive reframing, and co-construction of knowledge. These features present an opportunity to enhance healthcare workforce training, especially in psychiatry due to the highly interpersonal and relational nature of clinical skills. SBE can provide a unique opportunity for people with lived experience of mental disorders to be directly involved in clinical education. However, contentious issues have limited SBE’s adoption within psychiatry. The ability of simulated patients (SPs) to portray complex and contradictory cognitive, psychological and emotional features has been questioned. The validity of SBE to develop an empathetic understanding of the patient’s experience, to facilitate a comprehensive multiaxial diagnostic formulation, and to develop flexible interpersonal skills has been critiqued. Finally, relevance for training complex psychotherapeutic skills is still much debated, alongside ethical issues such as symptom induction in SPs. These controversies can be addressed through evidence, robust learning design, and high standards of practice. Well-designed simulated scenarios can promote an awareness of mental disorders and clinical skills, while developing shared guidelines and even libraries for simulated scenarios validated by expert psychiatrists, patients and students could be a rich training resource for SPs and educators. Debriefing conversations present a crucial opportunity to raise and reflect on nuances and complexity in mental healthcare, including complex interpersonal skills or the role of emotions in clinicians’ behaviour. Clinical educators can ensure tactful SP recruitment and maintain psychological safety to manage ethical issues. The holistic and reflexive nature of SBE aligns with psychiatry’s rich humanistic tradition, offering opportunities for increased application to meet workforce and clinical needs.